Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa Berkemampuan Rendah di Kelas III MI Birrul Walidain NW 2 Rensing: Teachers' Strategies in Improving Learning Motivation of Low-Ability Students in Class III MI Birrul Walidain NW 2 Rensing - Ahmad Izzudin (Pendidikan Al-Gafari, 2025)
Teachers are educational staff who greatly determine the learning process in schools. Teachers are one of the human components in the teaching and learning process, which plays a role in the effort to form potential human resources in the field of development. This study was conducted with the aim of: 1) to find out how the strategies and roles of teachers in improving the learning motivation of low-ability students in class III MI Birrul Walidain NW 2 Rensing, and 2) to find out what are the factors that cause the lack of learning motivation of students in class III MI Birrul Walidain NW 2 Rensing. This type of research is qualitative descriptive research, which aims to describe existing phenomena, both scientific phenomena and man-made phenomena can be in the form of activities, characteristics, changes, relationships, similarities and differences between one phenomenon and another. The methods used in this study are observation, interview and documentation methods. The results of this study are that: The learning motivation of students in class III, MI Birrul Walidain NW 2 Rensing is known that the students' learning motivation is already maximal. This is evident when the researcher observed directly, how the learning process is in the classroom, it is very clear how the role of the teacher in making students enthusiastic about participating in learning. Strategies in improving learning motivation of low-ability students used by teachers include: learning strategy planning, learning organization strategy, guidance strategy, learning implementation strategy, strategy for choosing learning methods and building a classroom environment. Factors causing lack of learning motivation include: factors such as not having breakfast, lack of socializing with peers, environmental influences, less conducive learning in the classroom, lack of attention from parents. So that it can hinder the motivation of these students to progress.